GBS with Bilateral plantar extensor – A case report (Bangladesh Journal of Neuroscience, 2015)
GBS is an immune mediated polyradiculoneuropathy classically characterized by acute symmetrical ascending lower motor type weakness and areflexia. But sometimes, in axonal variants of GBS, reflexes are preserved or exaggerated. We report a case of GBS with bilateral extensor plantar response during the course of the disease. A 36- year-old male presented with acute quadriplegia with asymmetrical muscle weakness and extensor plantar response. Sensory, bowel and bladder function was intact. He was treated with intravenous methylprednisolone daily for 5 days without improvement. NCS revealed AIDP and AMAN variants of GBS. So, in any patient presenting with acute quadriplegia with extensor plantar response, GBS should be considered as differential diagnosis.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 42-44